If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+4)=4x+7-2x+1
We move all terms to the left:
2(x+4)-(4x+7-2x+1)=0
We add all the numbers together, and all the variables
2(x+4)-(2x+8)=0
We multiply parentheses
2x-(2x+8)+8=0
We get rid of parentheses
2x-2x-8+8=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 6x+26=5x-1 | | 9x-5=10x-14 | | 4x+26x-7=6(5x+9) | | -10+p/2=-12 | | x×x=63 | | x/8=3=12 | | b+2/3=7/3 | | b+2/3=4/1/3 | | g=68 | | -16=8v+2(v+7) | | X2+5x-31=5 | | 3(5x+4)-8x=7x-12 | | x/7=7.04/4 | | 7x+1+11x-18+5x+13=88 | | 0x+9=8x+4 | | 4(z-9)=17 | | 7z=42;z=8 | | 5x−10=90 | | x+9x=100 | | 5x+54=5x+32 | | y+6=17;y=11 | | 4x-2/6=7 | | 5x+54=10x+64 | | 1.2/36=0.3/n | | 5x+7-6x=8 | | 2a-8=4a-(2a+1) | | Y=X^2+13x-30 | | -a-15=50 | | 2w/3=18 | | y=2,500-15(N-8) | | 6n+15=45 | | 16w=8w+64 |